2019
DOI: 10.1109/jbhi.2018.2834551
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Pelvis and Femur Segmentation in Hip CT With a Novel Patch-Based Refinement

Abstract: Due to bone deformation and joint space narrowing in diseased hips, accurate segmentation for pelvis and femur from hip computed tomography (CT) images remains a challenging task. Therefore, the paper presents a fully automatic segmentation framework for the pelvis and femur in both of healthy and diseased hips. The framework involves three steps: preprocessing, coarse segmentation and refinement. It starts with a preprocessing procedure to extract the volume of interest (VOI) from original CT images. Then, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The findings of this study may be enhanced by automating the segmentation of volumes and derivation of ratios. Automatic segmentation of the femur has been widely reported on in recent years and indicates strong potential for our volume ratio measurements to become automated [14][15][16][17][18]. This meets the last of the criteria we set forth for this method.…”
Section: Discussionmentioning
confidence: 64%
“…The findings of this study may be enhanced by automating the segmentation of volumes and derivation of ratios. Automatic segmentation of the femur has been widely reported on in recent years and indicates strong potential for our volume ratio measurements to become automated [14][15][16][17][18]. This meets the last of the criteria we set forth for this method.…”
Section: Discussionmentioning
confidence: 64%
“…Compared to traditional CNN nets and manual segmentation [ 18 ], the segmentation time of the diseased hip joints using our proposed method was significantly reduced. Shinichi et al [ 4 ] showed a coarse-to-fine hip CT segmentation framework that consisted of regional growth-based preprocessing, conditional random field-based coarse segmentation, and patch-based refinement. Radiology experts expend considerable effort in completing the training samples.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative computed tomography (CT)-based 3D planning is essential for total hip arthroplasty. Precise localisation and segmentation of the hip joint on CT images are necessary to simulate the placement of joint implants [ 4 , 5 ]. CT images from diseased hips exhibit image degradation, noise, non-homogeneous intensities and obscure boundaries between the femoral head and acetabulum; because of these features, automatic CT hip-joint segmentation is challenging [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of methods have been implemented to surmount the problem of bone segmentation, ranging from thresholding techniques to graph-cut methods. [8][9][10][11] Current segmentation methods often require a "user-in-theloop" paradigm in order to manually correct segmentations to produce acceptable masks for FE modeling and/or their processing time is too long for clinical use. This lack of robustness is costly in terms of time and the need for a highly trained specialist to manually correct the segmentations.…”
Section: Introductionmentioning
confidence: 99%